Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1128/iai.00827-07
|View full text |Cite
|
Sign up to set email alerts
|

Localized Th1-, Th2-, T Regulatory Cell-, and Inflammation-Associated Hepatic and Pulmonary Immune Responses inAscaris suum-Infected Swine Are Increased by Retinoic Acid

Abstract: Pigs infected with Ascaris suum or controls were given 100 g (low-dose) or 1,000 g (high-dose) all-trans retinoic acid (ATRA)/kg body weight in corn oil or corn oil alone per os on days after inoculation (DAI) ؊1, ؉1, and ؉3 with infective eggs. Treatment with ATRA increased interleukin 4 (IL4) and IL12p70 in plasma of infected pigs at 7 DAI and augmented bronchoalveolar lavage (BAL) eosinophilia observed at 7 and 14 DAI. To explore potential molecular mechanisms underlying these observations, a quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 79 publications
0
42
2
Order By: Relevance
“…2 Survival curve after induction of AIH, followed by prophylactic and therapeutic treatment with Asc. *p<0.05 compared to control group Dawson et al 2009). Their components could act to induce a Treg response in the liver or lymphoid organs through IL-10 production, and consequently improve liver tissue and serum markers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…2 Survival curve after induction of AIH, followed by prophylactic and therapeutic treatment with Asc. *p<0.05 compared to control group Dawson et al 2009). Their components could act to induce a Treg response in the liver or lymphoid organs through IL-10 production, and consequently improve liver tissue and serum markers.…”
Section: Discussionmentioning
confidence: 96%
“…Ascaris lumbricoides infections in endemic regions were associated with a highly polarized Th2 cytokine response . Generation of regulatory T cells (Tregs) in the liver and blood was observed during ascariasis (Matera et al 2008;Dawson et al 2009). The anti-A.…”
Section: Introductionmentioning
confidence: 99%
“…cDNA for gene expression studies was prepared from colonic tissue (13). Briefly, 50 ng cDNA per reaction was used for quantitative PCR (qPCR) amplification with a commercially available kit (Abgene, Rochester, NY), and amplification was measured on an ABI7700 instrument (Applied Biosystems, Foster City, CA).…”
mentioning
confidence: 99%
“…CCL17 is a chemokine produced by epithelial cells and dendritic cells which binds to Th2 cells (Hartl et al 2009). Dawson et al (2009) reported significant higher CCL17 expression on day 7 PI in liver tissue of pigs given retinoic acid and infected with A. suum than in uninfected controls; however, to our knowledge, a significant upregulation due to A. suum infection alone has not previously been demonstrated for this chemokine. In agreement with our results, Geiger et al (2013) found infection with helminths was associated with higher CCL17 concentration in human serum and Burke et al (2011) reported higher CCL17 expression in lungs of Schistosoma japonicum-infected mice compared with uninfected controls.…”
Section: Disscussionmentioning
confidence: 44%